Company Profile Kantor Camat Talang Kelapa Kabupaten Banyuasin - Fadillah, Ridho Akbar; Ariati, Nining; Dhamayanti, Dhamayanti (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2024)
A company profile website is a website that displays information about the company's background, products or services, contact information, and brief news about the company. The Talang Kelapa Sub-District Office already has a website to convey information. Still, no administrative services can be done online on the website, so the community must come directly to the Talang Kelapa sub-district office to carry out administrative services. Due to the lack of information, many people need to learn about the Service Information and Profile of the Talang Kelapa Sub-District Office. With this situation, the researcher is interested in compiling this research activity by taking the title